ANALISIS MAKNA IDIOMATIK DALAM ALQURAN - Rahman, Abdur (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Research related to material objects can be classified as follows: idiom meaning and semantic studies. On the meaning of idioms based on what was explained in Abdul Chaer's writings, an idiom is an utterance whose meaning cannot be predicted. Then in the semantic study aspect is the linguistic aspect which contains sound structures as well as concepts and meanings. From research related to the meaning of idioms that are often found in various someone's works, one of which is a novel. However, after tracing the meaning of the idiom cannot be understood only through the words that make it up, it requires re-analysis. Besides that, based on the research that the researchers conducted, research on the meaning of idioms used in the Qur'an, especially in each sura of this semantic review, has never been studied. This article uses qualitative research which means descriptive-analytical research. Based on the data analyzed and collected, this research is included in the category of Library Research (library) which is often disclosed, namely theoretical studies. The analysis used in this study is interpretive approach, namely looking at texts that can express a meaning in the sentence. With this analysis, the researcher has provided data which is the basis for applying the theoretical framework previously described. The author has found that there are many patterns of idiomatic meanings in every translation of surahs in the Qur'an. However, due to the limitations of the author's abilities, the author only takes a few patterns of idiom meanings as part of the surahs in the Qur'an, which count as many as 20 idioms with different surahs.